Análisis de procedimientos para prevenir la filtración de datos mediante la implementación de controles de la norma ISO 27001 en el centro operativo local ECU 911 Babahoyo. - Pendolema Espinosa, Ariel Oswaldo (2024)
Demanding study examines the procedures implemented at the ECU 911 Babahoyo Local Operations Center to prevent data leakage through the application of ISO 27001 controls. An interview was conducted with the assigned head to analyze these procedures. The interview results revealed the implementation of physical and logical access controls, firewalls, intrusion detection systems, and encryption of sensitive data. Information security policies and incident management procedures were highlighted. Challenges were identified such as evolving malware, staff training and mobile device management. Weaknesses were noted in user authentication, password management and system monitoring. The possibility of certifying the center to ISO 27001 was discussed, which would entail additional controls, regular risk assessments and training programmes. This study found a solid basis for the execution, improving the information security, ensuring the confidentiality, integrity, and availability of critical information in the operation center. The study provides us a comprehensive analysis of information security procedures and initiatives to reinforce information protection at the ECU 911 Babahoyo Local Operation Centre.